FORMULATION DEVELOPMENT AND EVALUATION OF PRONIOSOMAL GEL OF ETHINYLESTRADIOL AND LEVONORGESTREL FOR ANTIFERTILITY TREATMENT - Chauhan, Shikha Baghel; Naved, Tanveer; Parvez, Nayyar (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The purpose of this research was to develop and formulate proniosomal gel drug delivery system of ethinylestradiol and levonorgestrel for antifertility treatment that is capable of efficiently delivering entrapped drug over an extended period of time. Methods: Ethinylestradiol and levonorgestrel are encapsulated in various formulations of proniosomal gel composed of various ratios of span surfactant, cholesterol, soya lecithin, and alcohol as aqueous phase prepared by coacervation-phase separation method. The prepared formulations characterized for drug encapsulation efficiency, size distribution, in vitro release studies, and vesicular stability at different storage conditions were carried. Stability studies for proniosomal gel were carried out for a few weeks. Morphological size and shape of the vesicles are characterized using optical microscopy and scanning electron microscopy (SEM). Stability studies for proniosomal gel were carried out for 3 months. Results: Morphological size and shape of the vesicles are characterized using optical microscopy and SEM, particles are found to be spherical, size of the particles is in the range of 46.4–80.6 nm, and permeation studies showed good control release for prolonged period of time. The encapsulation efficiency of proniosomal gel formulations is in the range of 74–80% and in vitro permeation studies proved that good amount of drug is permeated and has reasonably good stability characteristics as well. Conclusions: The results suggest that proniosomal gel formulations of ethinylestradiol and levonorgestrel may be used for transdermal delivery for antifertility treatment. The dried proniosomal formulation could act as a promising alternative to niosomes.